Efektifitas Kurma Ajwa dalam berbagai Penyakit - Zulfahmidah Zulfahmidah; Risna Sri Wahyuni. M; Afrina F.Bustan (Yayasan Citra Cendekia Celebes, 2021)
The incidence of disease increases due to improper eating patterns, irregular eating patterns, consumption of processed foods except for the fruits of the food consumed. According to WHO statistics on diabetes mellitus, heart disease and ischemic stroke are the leading causes of death globally. Fruits are highly recommended by WHO to improve public health and public welfare. In building the health and well-being awareness of the past two decades significant progress has been made in the study of bioactive compounds in dates to find their immediate effects on human health. Dates Ajwa (Phoenix dactylifera L.) is a fruit that grows in many Arab countries, especially the city of Medina, Saudi Arabia. Based on several studies, dates have various phytochemical contents such as kumarat acid, ferric acid, flavonoids, phenolics, sterols, procyanidins, anthocyanins, carotenoids, vitamins and minerals that function as antioxidants, antihyperlipidimics, hepatoprotective, antimutagenic, antiinflammatory, nephroprotective and many other benefits in protecting the body from various diseases. Ajwa dates contain a high percentage of carbohydrate fiber (44-88%), dietary fiber (6.4-11.5%), fat (0.2-0.5%), protein (2.3-5.6 %), minerals and vitamins; also contains several fatty acids including palmic, oleic, linoleic and linolenic acids. Based on the description above, the researcher is interested in further studying the benefits contained in the Ajwa Dates.